Association between Physical Activity with Burnout Syndrome After the Second Wave of the COVID-19 Pandemic in Health Workers at RSD dr. Soebandi Jember - Dilar Bambang Sudito; Ancah C N Marchianti; Adelia Handoko (Faculty of Medicine, Universitas Jember, 2024)
Health workers have a key role in handling the COVID-19 pandemic. Working in a stressful environment can affect the emotional stability of health workers and can trigger burnout syndrome. Physical activity is one of the factors that can trigger burnout syndrome. Therefore, this study was conducted to analyze the relationship between physical activity and the incidence of burnout syndrome after the peak of the second wave of the COVID-19 pandemic among health workers at RSD dr. Soebandi Jember. This cross-sectional analytic observational study conducted from November to December 2021 was attended by 84 doctors and nurses working at RSD dr. Soebandi. The data were obtained using the Global Physical Activity Questionnaire and the Maslach Burnout Inventory. Ordinal logistic regression analysis showed a significant relationship between work activities and the level of burnout syndrome (p = 0.04). The effect of physical activity on burnout syndrome in this study was 32%. Our recommend is that further research is needed on the factors that can affect burnout syndrome with more objective research methods so that more valid results are obtained.